Cooperative Learning Model Type STAD for Improving Students' Skills in Determining Main Ideas of Paragraphs - Tamam, Badrut; Nurhikmah, Nurhikmah (Jurnal Dieksis ID, 2023)
Improving students' skills in determining the main ideas of paragraphs through the Cooperative Learning Model Type STAD which is based on extracting students' prior experiences and knowledge. The purpose of this study was to identify and improve the skills of determining the main ideas of paragraphs through the Cooperative Learning Model Type STAD. This research is an action research (action research), because the research was conducted to solve learning problems in the classroom. The research subjects were 28 Class VI students at Prambon Datangan Elementary School for the 2021/2022 Academic Year, in the material of Non-fiction Texts. Data collection techniques used in research are a). Observation of attitudes, with direct observation sheets to find out the activities of teachers and students in the ongoing learning process according to the existing cycle b). The Skills Test discovers the main ideas of students in the form of short answers. This study uses a qualitative descriptive analysis technique. Cooperative Learning Model Type STAD has a positive impact on improving student achievement as indicated by an increase in student mastery in each cycle, namely cycle I (60.71%), cycle II (75%), cycle III (89.29%). Based on the results of data analysis using percentages and skills in completing Indonesian language questions, it was concluded that the skills in determining the main ideas of paragraphs through the Cooperative Learning Model Type STAD increased, thus students were able to achieve the specified Minimum Mastery Criteria (KKM). The findings in this study are Cooperative Learning Model Type STAD has a positive impact on cooperation between students, this is shown by the existence of responsibility in groups where students who are more able to teach their less capable friends.